1997
DOI: 10.1074/jbc.272.32.20275
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Novel Heparin-binding Growth Factors in Uterine Secretory Fluids

Abstract: Uterine growth factors are potential effector molecules in embryo growth signaling pathways. Pig uterine luminal flushings contained a heparin-binding growth factor (HBGF) that required 0.8 M NaCl for elution from heparin columns and was termed HBGF-0.8. This factor, which was heat-and acid-labile and of M r 10,000 as assessed by gel filtration, stimulated DNA synthesis in fibroblasts and smooth muscle cells but not endothelial cells. Two forms of HBGF-0.8, termed HBGF-0.8-P1 and HBGF-0.8-P2, exhibited differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(71 citation statements)
references
References 39 publications
2
68
1
Order By: Relevance
“…Module IV resembles the Cterminal cystine-knot domain of several extracellular proteins including von Willebrand factor and mucins. Sequence similarities to heparin-binding motifs are also found within this domain (69). In CTGF, the C-terminal cystine knot domain is sufficient to mediate cell adhesion in a divalent cation-and heparin-dependent manner (70).…”
Section: Discussionmentioning
confidence: 99%
“…Module IV resembles the Cterminal cystine-knot domain of several extracellular proteins including von Willebrand factor and mucins. Sequence similarities to heparin-binding motifs are also found within this domain (69). In CTGF, the C-terminal cystine knot domain is sufficient to mediate cell adhesion in a divalent cation-and heparin-dependent manner (70).…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of CCN2 were detected in pig uterine flushings resulting from in utero proteolytic digestion of the full-length protein (41)(42)(43). In rats, an N-terminally truncated CCN3 form predominates in brain tissue and in cerebrospinal fluid (44).…”
Section: Discussionmentioning
confidence: 99%
“…This protein, initially identified in the conditioned media of HUVEC (Bradham et al, 1991), is characterized by a modular structure with four distinct domains including insulin-like growth factor binding protein, von Willebrand factor type C, TSR-1 repeat, and COOH-terminal domains (Bork, 1993). Several studies indicated that CTGF is mitogenic and a chemotactic factor for cultured fibroblasts that has been implicated in wound healing (Igarashi et al, 1993), fibrotic disorders (Igarashi et al, 1996), and uterine function (Brigstock et al, 1997). Further studies described that CTGF displayed mitogenic activities for endothelial cells (Shimo et al, 1998) and promoted angiogenesis (Shimo et al, 1999).…”
Section: Discussionmentioning
confidence: 99%